2020
DOI: 10.1155/2020/6020247
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling by UPLC–Orbitrap–MS/MS of Liver from C57BL/6 Mice with DSS-Induced Inflammatory Bowel Disease

Abstract: Liver disorder often occurs in patients with inflammatory bowel disease (IBD); however, the changes in IBD-induced liver disorder at the intrinsic molecular level (chiefly metabolites) and therapeutic targets are still poorly characterized. First, a refined and translationally relevant model of DSS chronic colitis in C57BL/6 mice was established, and cecropin A and antibiotics were used as interventions. We found that the levels of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6 in the liver tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Recently, it has been reported that many IBD patients also suffer from a secondary liver injury ( 43 ). Consistent with previous studies, the hepatic histological damage was observed in DSS-induced murine colitis model ( 43 , 44 ). AST and ALT always seemed like sensitive indicators to access the hepatic damage ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that many IBD patients also suffer from a secondary liver injury ( 43 ). Consistent with previous studies, the hepatic histological damage was observed in DSS-induced murine colitis model ( 43 , 44 ). AST and ALT always seemed like sensitive indicators to access the hepatic damage ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the differences in gut microbiota and serum metabolites in different groups, principal component analysis (PCA), and orthogonal partial least squares discriminant analysis (OPLS-DA) were performed and the over fitting of the model is verified by cross-validation (permutation test) using SIMCA-P (16.0.2, Sartorius Stedim Data Analytics AB, Umea, Sweden) ( 23 ). Then, univariate statistical analysis was used to screen metabolic markers with significant differences in accordance with our previous study ( 24 , 25 ). Briefly, based on OPLS-DA, the variable importance in the projection (VIP)>1, the relative abundance fold change of the metabolites of <0.5 or >2, and a p-value <0.05 were defined as differences.…”
Section: Methodsmentioning
confidence: 99%
“…The primary bile acid biosynthesis and steroid biosynthesis were similar to the previous time-points, which might be caused by the aforementioned mechanisms. Regarding steroid hormone biosynthesis and arachidonic acid metabolism, these 2 pathways are well-known for their active roles in inflammation [ 46 47 ]. During this period, eggs of parasite were produced and released to intestinal lumen, leading to inflammation of the organ.…”
Section: Discussionmentioning
confidence: 99%